Strategi Adaptasi Dampak Perubahan Iklim Terhadap Pembangunan Infrastruktur Ketenagalistrikan Di Wilayah Kalimantan Timur - Rachman, Fandi Nufinda; Hermana, Joni; Syafe'i, Arie Dipareza; Assomadi, Abdu Fadli (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Climate change is a global issue that affects various sectors, including the electricity sector, with one of the impacts of climate change being the increased risk of landslides influenced by rainfall, land use, slope gradient, and soil type. This research aims to assess the landslide risk in East Kalimantan on electricity infrastructure and formulate adaptation strategies for these landslides. The research method is a quantitative analysis and spatial approach by combining historical data and climate projections up to the year 2060 using the CMIP6 dataset scenarios SSP2-4.5 and SSP5-8.5. Data processed using Geographic Information System (GIS) to produce landslide risk maps for both current conditions and projections. The determination of adaptation strategies is carried out through a combination of SWOT Analysis and Analytical Hierarchy Process (AHP) methods. This research shows that the projection of landslide risk class areas in most parts of East Kalimantan is predominantly in the moderate risk class with an area of 58.16% and the high-risk class with an area of 26.43%. The priority strategies for landslide adaptation in the development of electrical infrastructure are chosen based on the analysis of three aspects: the optimization of DPT development and other supporting technologies in a planned and integrated manner, the preparation of a roadmap for prioritizing the reduction of extreme operational risk points as part of efforts to adapt to the projected increase in landslide risk, and the utilization of evaluation results from periodic monitoring and field inspections to support risk-based electrical infrastructure development planning.